Online peer motivational feedback in a public speaking course - Aminabibi Saidalvi; Adlina Abdul Samad (Penerbit Universiti Kebangsaan Malaysia, 2019)
Providing peer feedback is commonly practiced in teaching and learning of public speaking courses. However, there is limited research examining peer motivational feedback in an online setting. This study adopted a qualitative, descriptive approach using document analysis to investigate the frequencies of peer motivational feedback which students’ use in a public speaking course within an e-learning system of a local university. In addition, the specific public speaking skills and the nature of the feedback offered by students were also examined. Twenty-three final year undergraduate students video recorded their speeches, uploaded their videos, offered and received online peer feedback in the e-learning platform. All of the recorded online peer feedback went through a thorough classification process to identify, arrange, and systemize into the specified types of feedback. The data was examined at three levels of analysis to ensure concrete conclusions were drawn. Frequencies and examples of online peer motivational feedback were also presented. The results indicated that students provide relatively more motivational feedback on delivery and voice control skills, while paying less attention to language and proficiency skills. The process of giving and receiving feedback has acted as individualized feedback in which peers helped clarify the goal, criteria and expected standards of good performance. Thus, this study suggests that online peer motivational feedback could be used as a form of practice in the teaching of online public speaking courses due to its ability to motivate and sustain students’ interest in learning public speaking while creating a student-centered learning environment.